Analisa Keberhasilan Program Pelatihan menggunakan Webinar di Masa Pandemi Covid-19 - Diana Silaswara; Rinintha Parameswari; Agus Kusnawan (Komunitas Dosen Indonesia, 2021)
The pandemic period has changed many things, including the implementation of training that is usually done face-to-face or offline (outside the network) to online training (in the network). This study was made to determine the level of success of the training program (Y) using webinar media in terms of Class Management (X1) and Training Program (X2). This study uses Multiple Linear Regression analysis tools by processing questionnaires from all respondents, where valid respondents are those who have attended training using webinar media. Questionnaire answers from 64 valid respondents were first processed with classical assumption tests (validity, reliability, normality, linearity and heteroscedasticity) to find out valid and consistent statements, then correlation analysis, multiple linear regression and F-test were carried out. The result of this research is that the independent variable (class management and training program) has a significant positive effect on the dependent variable (training program success). These two variables affect 66.3% of the success of training through webinars, and the remaining 33.7% is influenced by other factors.